First standard for increased zinc content in wheat, maize and rice grain for food for human consumption published by British Standards Institution - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The standard specifies requirements for zinc-enriched maize, rice, and wheat for consumption. It includes requirements for levels of zinc for different grades of grain; sampling guidance; and labelling and packaging.